THE ISTINBAT METHOD OF MUHAMMAD BIN SHAHIH AL-UTSAIMIN: THE PROHIBITION OF REFUSING A MARRIAGE PROPOSAL BECAUSE OF STUDYING - Nurul Izzati, Nurul; Azwar, Zainal (Zawiyah: Jurnal Pemikiran Islam, 2024)
Marriage is "half of the religion" which plays a central role in the lives of individual Muslims. On the other hand, education is an important principle in Islamic teachings, as explained in the Qur'an and Hadith. In today's modern society, the phenomenon of Muslim women finding it important to pursue higher education and build a career before marriage. However, a controversy arises; is it permissible in Islam to reject a marriage proposal in favour of education or career? One of the muftis of Saudi Arabia, Shaykh Muhammad bin Shalih Al-Uthaimin, forbids it. This type of research is conceptual using a library research approach. Primary data is obtained from the opinion of Shaykh Muhammad bin Shalih Al-Uthaimin, secondary data is obtained from books, articles, and other scientific works relevant to the discussion. The results showed that Al-Uthaimin used the istinbath method based on the text of the Qur'an, the hadith of the prophet about marriage, and qaul shahabi. The results of the analysis also highlight the importance of pre-marriage agreements, especially with respect to education and career, to build a harmonious marriage. Al-Uthaymeen's statement on higher education being "not needed by the ummah" is quite controversial in the dynamic life of society. Al-Uthaymeen's opinion considers maslahah and Islamic principles in decision-making, while still respecting individual rights. This shows that within Islam, there are diverse views that can serve as a basis for modern society to make decisions in line with their religious values and goals.